HUBUNGAN ANTARA DISTRIBUSI FITOPLANKTON DENGAN KUALITAS PERAIRAN DI SELAT ALAS, KABUPATEN SUMBAWA, NUSA TENGGARA BARAT - I Nyoman Radiarta (Bumi Lestari Journal of Environment, 2013)
AbstractPlankton (phytoplankton and zooplankton) has an essential factor for aquatic ecosystem,because plankton is a primary food source for aquatic animals. This study was carried outin the Alas Strait, Sumbawa Regency on May 2012. Based on the data collected from 32stations, phytoplankton distributions (abundance and ecology indexes), water qualitycondition, and relationship between them were examined. Phytoplankton identificationresults show that a total of 25 species was found, and that species were classified into sevenclasses. Bacillariophyceae (diatom) was the dominant class found in the study area. Pearsoncorrelation indicated that water temperature, transparency, salinity, nitrate, and phosphatewere the parameters significantly affected on phytoplankton distribution and abundance.The results from this study could contribute on the development marine aquaculture in thisregion in term of pearl aquaculture development.